Settlement Dynamics and Factors Affecting Residence Selection in Population Density Settlements - M Fikri Amrullah; Endratno Budi Santosa; Muhammad Ansarullah S. Tabbu (JAMBURA GEO EDUCATION JOURNAL, 2023)
Settlements are one of the fundamental necessities of life. The functions of settlements go far beyond just providing a place for rest and shelter. Settlements serve as spaces where social interactions occur, relationships between individuals and groups develop, and community identities are formed. Ngagelrejo is located in the densely populated Wonokromo district of Surabaya, and despite its high population density, it is an area that is in great demand for residential purposes. When considering land ownership status, the entire area consists of land without citizen ownership titles, commonly referred to as "surat ijo" or green certificates. The purpose of this research is to understand the reasons why people choose to reside in densely populated areas. The research methodology employed is a qualitative phenomenological approach. Data were collected through interviews, observations, and documentation. Triangulation and in-depth interviews were conducted to ensure the validity of the data. The results of the study indicate that the choice of living in a densely populated area is primarily influenced by strong family and friendship bonds. The location of the residence is relatively close to workplaces, providing convenience and compatibility with the surroundings. Additionally, the price of land in this area is lower compared to other areas in the city of Surabaya.